Impact of refugee population on development: A comparative analysis for the case of host economies - Mohamed Kouni (Review of Economic Perspectives, 2018)
This study was carried out to investigate the relationship between refugees and development in host economies from a macroeconomic point of view. The results obtained show that this relationship is non-linear. The empirical results demonstrate that refugees have a positive and significant direct effect in high and lower-middle-income countries. A positive and significant indirect effect of refugees through labor force and RD channels is also present in the same groups. In upper-middle-income and low-income countries, the direct effect of refugees is negative and significant. Similarly, the indirect effect of the refugee population on development through labor force channel is also negative and statistically significant. However, the indirect effect of refugees through RD channel is statistically significant only for the low-income country group.
Keywords: O1; C32; O4; F22; 330; Economic development; GMM-method; growth; refugees